Bullfighting and Masculinity in Jorge Gutierrezs The Book of Life - Leendert Farrel Saimima; Sri Mulyani (Journal of Language and Literature, 2018)
This study is conducted to analyse the masculinity in Jorge Gutierrezs The Book of Life. The study is also conducted to discuss the variety of masculine characteristics within The Book of Life. The film takes place in a little Mexican town called San Angel where the protagonist, Manolo Sanchez, must choose between his family heritage to become the next Sanchez bullfighter or to become himself in his own image. The main objectives of this study are to explore the characters environmental structure, to distinguish the different characteristics of masculinity between them, and to relate masculinity with bullfighting in The Book of Life. This study uses gender and film approach. Gender approach is used particularly on masculinity since it is the primary discussion in this thesis while film approach is used to aid the researcher to determine where the masculinity is shown in The Book of Life. The method of this research is conducted through film and script analysis. Specific shots and lines from the script are analysed then discussed with the theories regarding masculinity and film.The result shows that Manolos masculine characteristics predominantly lies on Male Sex Role Strain, homosexual masculinity, and imposed environment. Meanwhile, Joaquin and Carlos shares the same masculine characteristics; they dominate the Male Sex Role Identity in all four themes and have the same hegemonic masculinity. Though their environment is nothing alike, Joaquins selected environment and Carloss constructed environment proved to be more masculine than Manolo. From these, the relations between the masculine characteristics particularly on Plecks Male Sex Role Identity and bullfighting shows that the various mise-en-scne displays the facial expressions of Manolo and Carlos frequently on scenes where the activity of bullfighting occurred. The framing language is dominated between MS (Medium Shot) and ECU (Extreme Close-Up) shot. Lastly, the continuity editing in The Book of Life is more dominant in the 180o Rule and Shot/Reverse Shot.Keywords: masculinity, gender study, film study